2022
DOI: 10.1142/s0129183123500195
|View full text |Cite
|
Sign up to set email alerts
|

Application of computational fluid dynamics for detection of high risk region in middle cerebral artery (MCA) aneurysm

Abstract: In the recent decades, the main reason for the high death rate is related to cardiovascular disease and stroke. In this paper, numerical studies have been done to investigate the hemodynamic effects on the rupture of middle cerebral artery (MCA) in different working conditions. In this work, the effects of the blood viscosity and velocity on the pressure distribution and average wall shear stress (AWSS) are fully investigated. Also, the flow pattern inside the aneurysm is investigated to obtain the high-risk r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Besides, the geometric parameters of aneurysms i.e. location and size have a great influence on the rupture of aneurysms 15 , 16 . The main challenge for the investigation of cardiovascular disease is the accessible data for the measurement of the blood characteristics i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the geometric parameters of aneurysms i.e. location and size have a great influence on the rupture of aneurysms 15 , 16 . The main challenge for the investigation of cardiovascular disease is the accessible data for the measurement of the blood characteristics i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the relationship between aneurysm geometrical features and hemodynamic characteristics has become a subject of intense research in the field of vascular biomechanics 4 , 5 . Two key hemodynamic parameters that have been widely investigated are wall shear stress (WSS) and oscillatory shear index (OSI).…”
Section: Introductionmentioning
confidence: 99%
“…The formation and growth of the cerebral aneurysm is the mainly related to the blood rheology and characteristics. The early reports have shown that the blood flow features of Wall shear stress (WSS) and OSI have great impact on the rupture and bleeding of the cerebral aneurysms 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The formation and growth of the cerebral aneurysm is the mainly related to the blood rheology and characteristics. The early reports have shown that the blood flow features of Wall shear stress (WSS) and OSI have great impact on the rupture and bleeding of the cerebral aneurysms 3,4 .The advance in the computational techniques has enabled scientists to calculate this hemodynamics on the wall of the aneurysm 5,6 . Besides, technique of the magnetic resonance angiography (MRA) and computed tomography angiography (CTA) offer valuable information on the shape and feature of the real three-dimensional aneurysm which is essential for the computational modeling.…”
mentioning
confidence: 99%